COD REMOVAL PERFORMANCE USING COMBINATION OF SPENT COFFEE GROUNDS ACTIVATED CARBON AND RIVER SAND AS FILTRATION MEDIA IN TOFU INDUSTRIAL WASTEWATER - Arief Rahman; Mulyadi Abdul Wahid; Sapriyadi (Indonesian Journal of Environmental Sustainability, 2025)
Tofu industrial wastewater contains a high level of chemical oxygen demand (COD), which may cause negative impacts if not treated before being discharged into the environment. Filtration is one of the simple and effective methods for COD removal in tofu industrial wastewater, utilizing filtration media such as sand and activated carbon. The objective of this research is to evaluate the performance of spent coffee grounds (SCG) activated carbon and river sand as filtration media in COD removal from tofu industrial wastewater. The research was carried out using a dual media filtration unit composed of SCG activated carbon and river sand, with media thicknesses of 15 cm and 30 cm, respectively. The results show that the combination of SCG activated carbon and river sand as filtration media can reduce the COD level in tofu industrial wastewater from 928 mg/L to 307 mg/L (66.92%), although it still does not meet the quality standard (300 mg/L). Based on the findings, it can be concluded that the combination of SCG activated carbon and river sand has the potential to lower COD levels in tofu industrial wastewater, but further improvement is required to enhance its effectiveness.